Taming Predatory Lending for a Resilient Financial System and Economic Growth - Kiiru, Joy (University of Nairobi, 2020)
This policy brief is critical, especially in the wake of the 2019 financial access survey that showed that the percentage of people with access to credit services was 82.9 per cent, up from 26.7 per cent in 2006 and 75.3 per cent in 2016. The same survey found that financial health (the ability to cope with unexpected financial demands) was worsening. Much of the access to credit is fuelled by a proliferation of lenders using mobile phone technology to give quick, small loans with terms that are otherwise unfair to the wellbeing of the borrower. This amounts to predatory lending, a lending practice with unfair or abusive loan terms on a borrower. It also amounts to a coercive practice that convinces a borrower to take a loan that they can do without. In this research, we focus on lending systems targeting the poor, to give policy recommendations for a healthy and resilient credit system in Kenya.